Emigration in the Republic of North Macedonia: indicators and estimations - Trpkova-nestorovska, Marija (Faculty of Economics-Skopje, 2019)
Emigration is one of the most serious problems that is threating the country. Large portion of the population is leaving the country in a process that lasts for decades. The consequences can be felt by severe lack of labor force in professions such as doctors, other medical personnel, IT professionals, accountants, builders, drivers, worker etc. With lack of formal reporting for emigration and immigration in the country and legislative that could regulate these matters it is difficult to estimate the scope of these mechanical movements. This paper offers an approach where the number of enrolled pupils in primary and secondary school are used to confirm their relationship with the number of emigrants and calculate the estimates of current population, population decline in the past decades and average annual loss of population. Using regression model the relationship between variables have been confirmed and estimates are made corresponding with those made by international institutions such as World Bank and OECD.
Keywords: emigration, enrolled pupils, geometrical rate of growth/decline